Stable and Tunable Single-Longitudinal-Mode Erbium-Doped Fiber Triple-Ring Laser With Power-Equalized Output - Chien-Hung Yeh; Jhih-Yu Chen; Hone-Zhang Chen; Jing-Heng Chen; Chi-Wai Chow (IEEE Photonics Journal)
In this demonstration, we propose and investigate a stable and tunable single-longitudinal-mode (SLM) erbium-doped fiber (EDF) ring laser structure. Here, in order to achieve the SLM output, the “eye-type” triple-ring scheme is designed in this EDF laser to suppress the densely spaced longitudinal modes. In the measurement, the output power and optical-signal-to-noise ratio (OSNR) are between 8.35 and 8.92 dBm and 33.2 and 35.7 dB, respectively, in the wavelength range of 1530 to 1560 nm. The proposed EDF laser architecture not only has free tuning step but provides stabilized and flattened output power spectrum as well.